Safe removal of an epidural catheter 72 hours after clopidogrel and aspirin administrations guided by platelet function analysis and thromboelastography - Eric Glenn; Judson Mehl; Francis A Rosinia; Henry Liu (Wolters Kluwer Medknow Publications, 2013)
Management of neuraxial anesthesia/analgesia in anticoagulated patient can be challenging. The shortest safe time to remove epidural catheter, after a patient receives long-acting dual antiplatelet agents (clopidogrel and aspirin), is unclear. American Society of Regional Anesthesiology (ASRA) guidelines recommend seven days interval for the epidural placement after clopidogrel administration. However ASRA Guideline did not specify the time for epidural catheter removal, and did not specify how much time elapse necessary after dual antiplatelet therapy with clopidogrel and aspirin. We report a case of safe removal of epidural catheter 72 hours after oral dose of clopidogrel and aspirin with a normal platelet function analysis and normal thromboelastography before removal.